The Influence of Work Motivation, Work Ethos, and Work Discipline on Employee Performance at Assalaam Hypermarket - Lestary, Febrianti T.; Fuadi, Djalal (Universitas Muhammadiyah Surakarta, 2023)
Employee performance is something that is very influential for the success and progress of the company. Thus, companies must be able to pay attention to what factors influence the performance of these employees. This study aims to determine the effect of work motivation, work ethos, and work discipline on employee performance at Assalaam Hypermarket. The research method used is quantitative with a descriptive correlational design. Thus, the researchers will use questionnaires related to work motivation, work ethos, work discipline, and employee performance. Furthermore, the researchers used a Likert Scale to measure the results of the data. The results of the research show that there is a positive and significant effect of work motivation, work ethos, and work discipline on the employee performance at Assalam Hypermarket.